Characterization of Inflammatory Bowel Disease in Elderly Patients: A Review of Epidemiology, Current Practices and Outcomes of Current Management Strategies - Peter Stepaniuk; Charles N Bernstein; Laura E Targownik; Harminder Singh (Canadian Journal of Gastroenterology and Hepatology)
The authors review and summarize the current literature regarding the epidemiology, clinical presentation and management of inflammatory bowel disease (IBD) in elderly patients.